Surgical treatment of disloced fracture of the scapula column and glenoid: A 22-year follow-up - Mladenovic, Desimir; Mladenović, Marko; Stojiljković, Predrag; Micić, Ivan; Karalejić, Saša (Vojnosanitetski pregled, 2015)
Introduction. Most scapular fractures are caused by high-impact blunt injuries, often as the result of motor vehicle accidents, fall from height, etc. In 80% to 90% of cases, scapula fractures are associated with multiple injuries (clavicle fracture, rib fractures, humeral fracture, pulmonary injury, brachial plexus injury). Case report. We presented scapular fracture in a 27-years-old male who had sustained a work-related injury when a ground soil brick machine pressed him. Fracture line was identified on radiotherapy and computed tomography scan from the distal scapular angle enclosing scapular neck. The whole lateral part of the scapula was dislocated laterally from the scapular body. Scapular fracture was treated operatively. The posterior approach was used for reposition, while for fixation after reposition we used two Blunt clamps. We presented functional outcome 22 years after the injury and the surgical treatment. The patient can perform all physical activities, still works, and there is no need to remove the ostheosynthetic material as it causes no discomfort nor problems. The strength of the shoulder muscles is estimated as physician as the grade 5. Conclusion. Displaced intra-articular fractures of the scapula should be treated operatively, with open reduction and internal fixation.